Bactérias resistentes e multirresistentes a antibióticos nos pacientes internados em uma UTI de adultos de hospital universitário brasileiro - Carvalho, Rodolfo Henriques de (2007)
Nosocomial infections caused by antibiotic resistant bacteria represents a substantial problem due to increasing in mortality, morbidity and health-care costs, especially in intensive care units. This study evaluated the frequencies of epidemiologically important antibiotic resistance phenotypes, recovered from ventilator-associated pneumonia (VAP) in critically ill patients and urinary tract infection (UTI) and bloodstream infections (BSI) in critical and non-critical patients. An one year study was performed in the adult intensive care unit (AICU) of the Clinical Hospital (CH) of Federal University of Uberlândia, where clinical specimens were obtained for diagnosis of VAP and UTI; moreover, the laboratory of the CH provided data that was used to define all the cases of BSI and UTI in non-critical units; additionally, a monthly inquiry of the antimicrobials consumption was carried through in AICU at the period of the study. Coagulase-negative staphylococci predominated as etiological agent of BSI in critically ill (24.6%) and non-critical (30.6%) patients, with frequency of 60,0% of oxacilin-resistant coagulase-negative staphylococci; Klebsielleae (23.4%) and E. coli (29.6%) were the major cause of UTI in critical and non-critical patients, respectively, with resistance above 20.0% to third generation cephalosporins and P. aeruginosa (42.0%) was the main etiological agent of VAP, with rates of resistance to imipenem and fluoroquinolons above 70,0%. The prevalence study of antibiotic consumption in the AICU pointed to cephalosporins (49.6%), followed by vancomycin (37.4%) and carbapenems (26.6%) as the most prescribed antibiotics in the unit. The comparison of our findings with other national and international studies demonstrated a highest frequency of antibiotic resistant phenotype in our hospital, in critical and non-critical units, especially among the Gram-negative bacterias, however, it was not observed a significant variation between the frequency of resistance phenotypes recovered from critical and non-critical units, what strongly suggests that these phenotypes had already spread in the hospital, except P. aeruginosa whose resistance to antibiotic was more expressive when recovered from critical patients than non-critical ones.